2007
DOI: 10.5194/angeo-25-303-2007
|View full text |Cite
|
Sign up to set email alerts
|

Coherent whistler emissions in the magnetosphere – Cluster observations

Abstract: Abstract. The STAFF-SC observations complemented by the data from other instruments on Cluster spacecraft were used to study the main properties of magnetospheric lion roars: sporadic bursts of whistler emissions at f ∼0.1−0.2f e where f e is the electron gyrofrequency. Magnetospheric lion roars are shown to be similar to the emissions in the magnetosheath while the conditions for their generation are much less favorable: the growth rate of the cyclotron temperature anisotropy instability is much smaller due t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
46
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 33 publications
1
46
0
Order By: Relevance
“…In particular, it means, that the wavelength is specified by kc/ω e ∼ 1, which is clear evidence of Gendrin mode waves and their importance for whistler wave emission. This aspect has also been discussed in the paper by Dubinin et al (2007).…”
Section: Summary and Discussionmentioning
confidence: 75%
“…In particular, it means, that the wavelength is specified by kc/ω e ∼ 1, which is clear evidence of Gendrin mode waves and their importance for whistler wave emission. This aspect has also been discussed in the paper by Dubinin et al (2007).…”
Section: Summary and Discussionmentioning
confidence: 75%
“…An important lesson we have learned is that the predictions of linear instability theory say very little about the wave characteristics under the conditions of nonlinear saturation and may even be misleading. Our main finding is that Gendrin modes and related oscillitons seem to play an essential role in characterizing the final nonlinear state of the system (Sydora et al, 2007;Dubinin et al, 2007;Stenzel et al, 2008;Verkhoglyadova and Tsurutani, 2009;Sauer and Sydora, 2010). In this respect many further applications (such as electron and ion cyclotron harmonic waves, multi-ion waves etc.)…”
Section: Discussion and Summarymentioning
confidence: 99%
“…Up to now, the most compelling measurements have been done using the whistler wave branch. In the paper by Dubinin et al (2007) the appearance of wave packets in the Earth's magnetosphere has been explained in terms of whistler oscillitons driven by temperature anisotropy. Subsequent kinetic simulations by Sydora et al (2007) have shown that during the nonlinear saturation of the temperature anisotropy instability a significant wave number shift (from large k values) to the Gendrin point (where phase and group velocity coincide) takes place accompanied by the formation of whistler oscillitons.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, evolution of electromagnetic turbulence is important to both space and laboratory plasmas and has been a topic of intense research for decades. Electromagnetic whistler turbulence in the intermediate frequency range, ⍀ i Ӷ Ӷ⍀ e , where ⍀ i͑e͒ are ion ͑electron͒ gyrofrequency, continues to be of interest to ionospheric, 1,2 magnetospheric, and solar wind plasmas [3][4][5] as well as to laboratory plasmas. 6,7 The purpose of this article is to show that the dominant nonlinear ͑NL͒ effect makes whistler turbulence in a low ␤ plasma, similar to that found in the near-earth space environment, a three-dimensional ͑3D͒ phenomenon in which the evolution of the turbulence is characterized by induced NL scattering.…”
Section: Introductionmentioning
confidence: 99%